DAMPAK EKOWISATA TERHADAP KESEJAHTERAAN MASYARAKAT DI KAWASAN WISATA AIR TERJUN KOTA BATU - eki permono; Arfida Boedirochminarni; M.Sri Wahyudi (Jurnal Ilmu Ekonomi JIE, 2019)
This study had a objective, that is : to analyze about fover the fuction of forest and the walfare in tourist area of Batu waterfall so it can be known are over the forest fuction commensurate with the well being og obtained by local communities. Analysis tools used are descriptive quantitative  using t-test, the results of this study showed people's income are changed, this can be seen from the average revenue of the society. Where the average income is Rp 770.000 growing up 77.99% to Rp 1,355,000. The social impact is assessed of changes in the quality and means of education. Improvement of facilities and quality of this became the catalyst so that the public send his son. Healthy life patterns society became better as well as the existence of a new business field that makes labor can be absorbed around the tourist areas. The negative impact of any missed over the function of the forest, that is because of the numbers of visitors to much adn resulted in noise at citizens when entering the rest time.Keywords : environmental impact, Batu waterfall, revenue, social impact, tourist development